A Novel Mechanism for Generating the Interferon Signature in Lupus: Opsonization of Dead Cells by Complement and IgM. Issue 12 (December 2016) - Zhuang, Haoyang; Han, Shuhong; Li, Yi; Kienhöfer, Deborah; Lee, Pui; Shumyak, Stepan; Meyerholz, Richard; Rosadzinski, Krzysztof; Rosner, Danielle; Chan, Annie; Xu, Yuan; Segal, Mark; et al.
Abstract : Objective: In vitro studies suggest that the type I interferon (IFN) signature seen in most lupus patients results from Fcγ receptor–mediated uptake of nucleic acid–containing immune complexes by plasmacytoid dendritic cells and engagement of endosomal Toll‐like receptors. The aim of this study was to reexamine the pathogenesis of the IFN signature in vivo. Methods: Lupus was induced in mice by injecting pristane. Some mice were treated with normal immunoglobulin or with cobra venom factor to deplete complement. The IFN signature was evaluated by polymerase chain reaction. The IFN signature also was determined in C4‐deficient patients and control subjects. Results: Wild‐type C57BL/6 mice with pristane‐induced lupus developed a strong IFN signature, which was absent in immunoglobulin‐deficient (μMT), C3 −/−, and CD18 −/− mice. Intravenous infusion of normal IgM, but not IgG, restored the IFN signature in μMT mice, and the IFN signature in wild‐type mice was inhibited by depleting complement, suggesting that opsonization by IgM and complement is involved in IFN production. Consistent with that possibility, the levels of "natural" IgM antibodies reactive with dead cells were increased in pristane‐treated wild‐type mice compared with untreated controls, and in vivo phagocytosis of dead cells was impaired in C3‐deficient mice. To examine the clinical relevance of these findings, we identified 10 C4‐deficient patients with lupus‐like disease and compared them with 152 C4‐intact patients and 21 healthy controls. In comparison with C4‐intact patients, C4‐deficient patients had a different clinical/serologic phenotype and lacked the IFN signature. Conclusion: These studies define previously unrecognized roles of natural IgM, complement, and complement receptors in generating the IFN signature in lupus.